The impact of climate change on the efficiency of agricultural crop cultivation in Rivne region. - Kupriyanchyk, I. (Land Management, Cadastre and Land Monitoring, 2025)
This article examines the impact of climate change on the efficiency of agricultural crop cultivation in Rivne Region, which serves as a representative area for studying adaptation processes under changing climatic conditions in northwestern Ukraine. It has been established that rising average annual temperatures, decreasing uniform precipitation, and more frequent droughts significantly affect the yields of major crops and cause their spatial differentiation. The study includes a spatial analysis of agricultural production, an assessment of climate-related risks across the administrative districts of the region, and an identification of regional differences in the effects of climatic factors. An economic evaluation of the efficiency of growing various crops under the new climatic conditions was conducted. The results indicate the need to adjust crop structure in favor of more adaptive and profitable crops such as potatoes, maize, open-field vegetables, and fruit and berry crops. An optimized structure of cultivated areas, adapted to current agro-climatic conditions of the region, is proposed. The study employs an interdisciplinary approach that integrates agro-climatic analysis, economic assessment, and spatial modeling. The findings can be used to develop strategies for adapting the agricultural sector to climate change, ensuring food security, and enhancing the economic resilience of agricultural production in Rivne Region and similar regions of Ukraine. Keywords: climate change; agriculture; economic efficiency; crop yield; agroclimatic risks; spatial analysis; crop structure; food security